Coastal Waste Identification as Part of Waste Management Efforts in Dusit Area, Balikpapan, East Kalimantan - Karnila Willard; Fitri Oktafiani (Indonesian Journal of Chemistry and Environment, 2025)
Coastal waste pollution remains a critical environmental issue that poses substantial risks to marine ecosystems and nearby communities. This study aims to identify the composition and volume of coastal waste found in the Dusit Beach area and to evaluate potential management strategies that support environmental sustainability and community empowerment. Using a field-based research approach, systematic waste collection was conducted on 18 May 2024, resulting in 27 sacks of waste that were subsequently sorted and analyzed. Plastic waste was identified as the most dominant category by volume, accounting for 48 percent of the total. The 13 sacks of plastic waste collected weighed 129.7 kg. These results indicate inadequate waste management practices and limited public awareness regarding proper waste disposal and segregation. Further analysis reveals that the significant amount of plastic waste presents opportunities to apply the 3R waste management concept (Reduce, Reuse, Recycle). Examples include eco-brick production, craft development, simple construction materials, and community-based waste bank initiatives to generate raw materials for recycling. Community involvement and empowerment in waste management are essential strategies to enhance public participation and generate additional economic value. Overall, the findings emphasize the need for an integrated and community-driven waste management system to reduce coastal pollution and promote sustainable development.